Spectral line list of potential cosmochronological interest deduced from new calculations of radiative transition rates in singly ionized thorium (Th ii). Issue 4 (18th June 2020) - Gamrath, S; Godefroid, M R; Palmeri, P; Quinet, P; Wang, K
ABSTRACT: In this work, we report a list of 91 strong Th ii spectral lines in the visible wavelength region that could be used as cosmochronometers in future investigations to determine stellar ages from thorium radioactive decay. This list was established on the basis of a pseudo-relativistic Hartree–Fock model including core-polarization corrections (HFR+CPOL) allowing us to compute the corresponding radiative decay parameters, the latter being found to be in good overall agreement with the most accurate experimental data when available. Besides this semi-empirical approach, the fully relativistic ab initio multiconfiguration Dirac–Hartree–Fock (MCDHF) method was attempted, showing large discrepancies with both the present HFR+CPOL and the most recent experimental oscillator strengths, although the calculated wavelengths from theoretical energy levels agreed with observed spectral line wavelengths within 2.4 per cent.